Financial Stability and Bank Capital: The Case of Islamic Banks - Daoud, Yomna; Kammoun, Aida (International Journal of Economics and Financial Issues, 2020)
The purpose of this research is to empirically analyze Islamic Bank's financial stability, which consists in assessing the possible relationship between the risk of default (measured by z-score) and capital ratios while considering specific internal bank determinants. A regression analysis is derived on an unbalanced panel data including 405 observations of 81 Islamic banks established in 22 counties during the period of 2010-2014. To this purpose, our bank-specific data are collected from the websites of each bank and Bankscope database. The results show that almost all determinants estimated in the empirical models have statistically significant effect on the stability of Islamic Banks. The regression results show that two capital ratios (Non-risk-weighted capital ratio and Risk-weighted capital ratio), banks' Size, loans to total assets, total deposit to total assets and overhead cost to total assets represent important predictors of bank stability in Islamic banking industry. The empirical results contribute to the comprehension of the relationship between bank-specific variables as well as macroeconomic indicators and the financial stability of the banking system. On the basis of these findings, some proposals could be useful for bank regulators supervisors to enhance and maintain the strength and stability of the Islamic banking sector. Compared to other studies, that conducts a comparative analysis of Islamic and conventional banks, this paper focus only on Islamic banks, so any findings will be more relevant to their business. Hence, it attempts to fill a significant gap in the literature by better understanding the stability and soundness of Islamic banks. Keywords: Financial stability, Islamic banks, z-score, capital ratio JEL Classifications: G21, G32 DOI: https://doi.org/10.32479/ijefi.10147